Evaluation of Gas Industry Competitiveness in the Foreign Market - Shcherbakova, Natalya S.; Nazarova, Yulia A.; Kirichenko, Olga S.; Gorunov, Oleg A.; Dubrovsky, Andrey V. (International Journal of Energy Economics and Policy, 2020)
The evaluation of the Russian oil and gas companies’ competitiveness in the foreign market under the tough market conditions is of particular importance as it is crucial to retain company’s current position and market share. The article makes qualitative and quantitative evaluation of Russian companies in the global gas market. To analyze the competitiveness of the gas industry company in the foreign market, the authors used a dynamic method of evaluating competitiveness coupled with a SWOT analysis. The dynamic evaluation method offers an opportunity to identify the basic factors that influenced the level of competitiveness of the entity under study and, accordingly, determine the main reserves for increasing its competitiveness. Based on the study conducted, recommendations were made on the increase in competitiveness in the current situation of unstable demand and volatile energy prices. By analyzing the PJSC Gazprom level of competitiveness, as well as its external and internal environment, indicators were identified the regulation of which will lead to the progressive development of the organization and increase in its competitiveness. The practical relevance of the study lies in the possibility to use both the research outcome and the proposed methods in a development strategy for the gas industry company. Keywords: advantages, competitiveness management, SWOT-analysis, oil and gas companies. JEL Classifications: L10, F23, N70 DOI: https://doi.org/10.32479/ijeep.10275